Community and Collaboration in a Shared Multi-space Office - Ansio, Heli; Käpykangas, Sari; Houni, Pia (Nordic Journal of Working Life Studies, 2020)
Open and shared work environments such as activity-based offices, multi-space offices and co-working spaces have become more popular in recent years. This paper reports the results of a qualitative case study of community and collaboration in a multi-space office shared by six publicly owned companies in Finland. Using interviews (n = 29) and participant observation, the study examines how collaboration and community are understood in the six companies, and how they change during an intervention process. We argue that even though a sense of community, collaboration and synergies are expected to arise from sharing an office space, they do not necessarily emerge spontaneously without effort on the part of management.